Dynamic balance is related to physiological impairments in persons with multiple sclerosis - Peebles, Alexander T. (Arch Phys Med Rehabil, 2017)
OBJECTIVES: To compare physiological impairments between persons with multiple sclerosis (MS) with a history of falls and persons with MS without a history of falls and to investigate the association between physiological impairments and dynamic balance. DESIGN: Cross-sectional study. SETTING: University motion analysis laboratory. PARTICIPANTS: Fifty-five persons with MS (27 recurrent fallers and 28 non-fallers). Participants were classified as fallers if they self-reported 2 or more falls in the previous six months. INTERVENTIONS: None. MAIN OUTCOME MEASURES: Physiological impairment was assessed with sensorimotor delays, spasticity, plantar cutaneous sensation, and the sensory, cerebellar, and pyramidal Expanded Disability Status Scale (EDSS) subscales. Dynamic balance was assessed using the average and variability of margin of stability and variability of trunk accelerations. RESULTS: Compared to non-fallers, fallers had lower plantar sensation, longer sensorimotor delays, more spasticity, and more impairment in the pyramidal and cerebellar EDSS subscales. Additionally, these impairments were all moderately to strongly correlated with worse dynamic balance. CONCLUSIONS: The present study highlights the multifactorial nature of instability in persons with MS. A better understanding of the physiological mechanisms of dynamic instability in persons with MS can be used to improve methods of monitoring disease progression, identifying which impairments to target through interventions, and appropriately evaluating intervention efficacy.